Insulin and insulin like growth factor II endocytosis and signaling via insulin receptor B - Giudice, J. (2013)
Background: Insulin and insulin-like growth factors (IGFs) act on tetrameric tyrosine kinase receptors controlling essential functions including growth, metabolism, reproduction and longevity. The insulin receptor (IR) binds insulin and IGFs with different affinities triggering different cell responses. Results: We showed that IGF-II induces cell proliferation and gene transcription when IR-B is over-expressed. We combined biotinylated ligands with streptavidin conjugated quantum dots and visible fluorescent proteins to visualize the binding of IGF-II and insulin to IR-B and their ensuing internalization. By confocal microscopy and flow cytometry in living cells, we studied the internalization kinetic through the IR-B of both IGF-II, known to elicit proliferative responses, and insulin, a regulator of metabolism. Conclusions: IGF-II promotes a faster internalization of IR-B than insulin. We propose that IGF-II differentially activates mitogenic responses through endosomes, while insulin-activated IR-B remains at the plasma membrane. This fact could facilitate the interaction with key effector molecules involved in metabolism regulation. © 2013 Giudice et al.; licensee BioMed Central Ltd.